The Impact of Self-Regulated Learning and Students’ Learning Styles on Their Learning Outcomes in Arabic Language - Faisal Mubarak; Muhammad Infithar Al Ahqaf; Mohamad Abdullah Alsaied (Universitas Islam Negeri Jurai Siwo Lampung, 2024)
Self-regulated learning refers to a student's ability to organize and control their learning process, while learning styles include individual preferences in processing information. This type of research is field research with a quantitative approach and ex post facto model. The population was of class XI at Senior High Schools in Banjarmasin, totaling 803 students. The sampling technique was simple random sampling, and 260 students were obtained. The data collection techniques used were questionnaires and documentation. Data analysis techniques include simple linear regression and multiple linear regression. The results showed that: 1) There is a positive and significant relationship between learning independence and Arabic learning outcomes. 2) There is a positive and significant relationship between learning style and Arabic learning outcomes. 3) There is a positive and significant relationship simultaneously between learning independence and learning styles in Arabic learning outcomes.